Genotypic characteristics of Gluconacetobacter hansenii LMG 1582 suggest its reclassification to a new species - Janja TRČEK (Acta Agriculturae Slovenica)
A strain of the acetic acid bacteria, purchased from the international culture collection as Gluconacetobacter (Ga.) hansenii LMG 1582, was studied in more detail using the molecular methods. The HaeIII- and HpaII-restriction profile of the PCR amplified 16S-23S rDNA spacer region were compared to the restrictions profiles of the reference strains of the acetic acid bacteria. The comparison has shown no similarity. The sequence analysis of the 16S rRNA gene exhibited 22 nucleotide differences between the strain Ga. LMG 1582 and Ga. hansenii type strain. The sequence showed the highest similarity (99.2 %) to Ga. europaeus, representing 9 nucleotide differences. The strain Ga. LMG 1582 is well separated from the other presently recognized species of the acetic acid bacteria also in the 16S rDNA based phylogenetic tree. All this suggests that the strain Ga. hansenii LMG 1582 might be reclassified into a new species.